Correction of gummy smile by superior repositioning of maxilla in Bangladeshi people (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2016)
Vertical maxillary excess is associated with gummy smile, incompetent lip,  bimaxillary proclination, Angle’s class-I or class-II malocclusion with or without retogenia. After proper evaluation preoperative orthodontic treatment was performed in every cases and superior repositioning of the maxilla by Le Fort-I osteotomy is presented. Three patients with maxillary excess associated with retrogenia or microgenia were treated with this technique in combination with genioplasty. The maxillary segment was repositioned a maximum of 7.0 mm superiorly at point A. The mandible autorotated anterosuperiorly to achieve sound occlusion. Point B moved 1.0–3.0 mm anteriorly and 5.0–8.0 mm superiorly. The pogonion moved 4.0 mm anteriorly in a case done without genioplasty and the pogonion moved maximum 8.0mm in case done in combination with genioplasty. All patients obtained sound occlusion and a good profile after the operation. Almost no skeletal relapse was observed during 3 years of postoperative follow-up. Amount of gingiva showing during smile was ranges from 5.0mm –7.0mm which was 0-2.0mm after superior repositioning of the maxilla.Ban J Orthod & Dentofac Orthop, April 2016; Vol-6 (1-2), P.1-5